Noteworthy Records of Birds from the Panua Nature Reserve, North Sulawesi - Jon Riley; Yusman Hunowu; Joris Mole; Michael F Wangko (KUKILA, 2003)
Panua Nature Reserve is the second largest terrestrial conservation area in North Sulawesi, located on the south coast of Sulawesi's north peninsula. We conducted surveys of the reserve between February and June 2000, including 241 km of line transect censuses, primarily in the dominant lowland evergreen rainforest. A total of 124 bird species were recorded, including 48 Sulawesi endemics, and l3 species (all but two endemic) that are considered by most authorities as Threatened or Near Threatened. In this paper we describe the habitats of the reserve and summarize observations of all l3 threatened species, as well as six other species for which our surveys clarify distribution or status within Sulawesi.